(untitled) (International Journal of Advanced Research in Computer Science, 2017)
The recent years research has shown a great interest in text mining leading to opinion mining and analysis of the social media postings. The influence of social media in opinion formation of public, is widely used in brand promotion. The casual public posts are classified . The sentiments are measured. A feedback loop is created. This paper intends to identify the sentiments behind the casual social media transcripts and convert the general viewers to potential visitors to confirmed client. This is a case study of tourism industry. In this study NER algorithm for opinion mining technique is applied to an eco tourist resort property domain. Here we are trying to discover consumer preferences about eco tourism, speciality features of the resort property and restaurant, from Facebook posts as reviews. The model created helps in determining the sentiment orientation of opinions and the feedback to improve the services offered which inturm increases the traffic. Keywords: Opinion Mining, Sentiment Analysis, Social Network, Text mining, Brand promotion